Blended binder system containing waste paper sludge ash (WPSA) and palm oil fuel ash (POFA) for solidification/stabilization (S/S) method in treating ceramic sludge / Mazni Mat Zin - Mat Zin, Mazni (2014)
Ordinary Portland cement (OPC) was the major binder used in Solidification/Stabilization (S/S) method. The problems created by cement industry in producing OPC such as emission of carbon dioxide to the environment and high energy used cause new alternative introduced through this study to replace OPC with other material to be act as a binder in S/S method. An experimental study of the use of an industrial by-product as a binder in (S/S) has been performed. The influence of the variable mixes composition of POFA and WPSA in producing blended binder system has been studied. The compressive strength and Toxicity Characteristic Leaching Procedure was used to evaluate the effect of POFA and WPSA to the solidified/stabilize ceramic sludge after 28 days of water curing. The sufficient compressive strength and significant reduction in heavy metal Cr,Pb,Ni, and Cu shows the potentiality of using POFA and WPSA in producing blended binder system in treating ceramic sludge